Reduction of trap and polydispersity in mutually passivated quantum dot solar cells - Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (ACS Applied Energy Materials, 2020)
Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport process. However, the ligand exchange process often resulted in reduced surface passivation, inhomogeneous QD fusion, and deterioration of energy band gap, which adversely impact their performance in solar cells. Here, we introduce a surface passivation strategy where the QDs are mutually passivated by the organic ligand 3-methyl mercapto propionate and inorganic halometallate ligands to develop a conducting QD ink. The mutually passivated QDs (MPQDs) show significant improvement in optoelectronic properties in maintaining the trap-free energy band gap and size monodispersity. The photovoltaic performance of MPQDs shows a 33% average increase in power conversion efficiency (PCE) over the conventional halometallate passivation to attain 9.6% PCE in MPQD solar cells. The improvements in photovoltaic parameters are corroborated by the reduction in density of the intermediate trap states and an increase in depletion width and diffusion length in MPQD-based solar cells.
Keywords: polydispersity; quantum dot; solar cells; surface passivation; trap states

Solution-phase hybrid passivation for efficient infrared-band gap quantum dot solar cells - Mahajan, Chandan; Sharma, Ashish; Rath, Arup K. (ACS Applied Materials & Interfaces, 2020)
The broad tunability of the energy band gap through size control makes colloidal quantum dots (QDs) promising for the development of photovoltaic devices. Large-size lead sulfide (PbS) QDs, exhibiting a narrow energy band gap, are particularly interesting as they can be used to augment perovskite and c-Si solar cells due to their complementary NIR absorption. However, their complex surface chemistry makes them difficult to process for the development of solar cells. The shape of the QDs transformed from octahedron to cuboctahedron as their size increases, a phenomenon guided by surface energy minimization. As a result, the surface properties change drastically for large-size QDs, which exhibit nonpolar (200) facets and polar (111) facets, as opposed to only (111) facets in small-size QDs. Recent advancements in solution-phase surface passivation strategies, used for the development of high-performance solar cells using the small size and wide band gap QDs, failed to translate a similar enhancement in the case of large-size and narrow band gap QDs. Here, we report a hybrid passivation strategy for large-size and narrow band gap QDs to passivate both (111) and (200) facets, respectively, using inorganic lead triiodide (PbI3-) and organic 3-chloro-1-propanethiol (CPT). By employing charge balance calculation, we identified the desired narrow band gap for QDs to complement the perovskite and c-Si absorption. The distinct choice of the organic ligand CPT enhances the colloidal stability of QDs in the solution phase and improves surface passivation to stop QD fusion in solid films. Photophysical properties show narrower excitonic and emission peaks and a reduction in the Stokes shift. Hybrid passivation leads to a 94% increase in the power conversion efficiency of solar cells and a 74% increase in the external quantum efficiency at the excitonic peak.
Keywords: infrared band gap; polydispersity; quantum dot; solar cells; surface passivation; trap states

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

High open-circuit voltage in lead sulfide quantum dot solar cells via solution-phase ligand exchange with low electron affinity cadmium halides - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Mitra, Anurag; Rath, Arup K. (JOURNAL OF MATERIALS CHEMISTRY A, 2023)
The deployment of colloidal quantum dots (QDs) in building high-performance solar cells and other optoelectronic applications relies on the passivation of unsaturated surface atoms through ligand engineering to attain a trap-free energy bandgap and strong QD coupling while maintaining the quantum confinement effect. Despite major advancements in surface passivation strategies, the open circuit voltage (V-oc) of lead sulfide (PbS) QD solar cells is limited by undesirable sub-bandgap states and high-bandtail states. The most advanced solution-phase ligand exchange strategy for PbS QDs depends on lead halide ligands, which improved the photocurrent and fill factor in QD solar cells significantly, but only an incremental change in V-oc is observed. Here we showcase a solution-phase hybrid ligand passivation strategy for PbS QDs using shallow electron affinity cadmium halide and thiol ligands. The cadmium halide ligand treatment results in the sub-monolayer substitution of surface Pb atoms by Cd atoms. The photophysical properties of QDs improve significantly to show intense band edge emission, diminished trap emission and reduced Urbach tail states. The photovoltaic devices built using cadmium halide-treated QDs show low reverse saturation current, which helps to attain a record 0.7 V V-oc (for a 1.28 eV bandgap) and 12.3% PCE.

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Solution-phase ligand engineering for all-quantum-dot near-infrared light-emitting diodes - Biswas, Arindam; Mitra, Anurag; Sharma, Ashish; Shinde, Dipak Dattatray; Dambhare, V. Neha; Sharma, Anjali; Mahajan, Chandan; Rath, Arup K. (ACS Applied Nano Materials, 2024)
Strong emission over a wide near-infrared (NIR) region makes lead sulfide quantum dots (QDs) a preferred material in building NIR light-emitting diodes (NIR-LEDs) for numerous applications. Narrow-bandgap emitter QDs blended in the matrix of high-band gap QDs offer a simple yet powerful architectural platform for building high-performance NIR-LEDs. So far, the all-QD-based blend architecture has been realized using a poorly controlled solid-state ligand exchange approach. Advanced solution-phase ligand exchange, which offers greater control over surface passivation, is yet to be realized in all-QD LED device construction. We observe that the solution-phase ligand exchange from the optimized lead halide and thiol ligand combination, used in high-performing QD solar cell construction, is inefficient in realizing efficient all-QD LEDs, which could have restricted the adoption of the solution-phase ligand exchange thus far. Here, we introduce an innovative dual-ligand strategy to build all-QD-based NIR-LEDs using an advanced solution-phase ligand exchange approach. Through ligand engineering of matrix QDs, we managed to improve photoluminescence quantum yield (40%), reduce trap density (10(14) cm(-3)), and prolong carrier lifetime (832 ns). The LED devices benefit from improved electronic properties and balanced carrier injection to yield 6% EQE and 7.7% PCE, which are six times higher than those of state-of-the-art ligands.
Keywords: electroluminescence; lead sulfide; ligand passivation; light-emitting diodes; near-infrared; quantumdots

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell